MATHEMATICAL MODEL OF NUTRIENT USE IN BIOFLOC SYSTEM VANAME SHRIMP TO MAXIMIZE FARMING PROFITS - Bufon, Yuan Lucky; Murnawan, Hery (Acitya Wisesa: Journal of Multidisciplinary Research, 2024)
Aquaculture is one of the alternative activities in increasing fisheries production. Shrimp is the commodity with the highest number of exports, which is 239.28 million kilograms. The key to the growth of cultured biota is by feeding nutrients in order to increase company profits. The purpose of this research is to determine whether nutritional formulas may reduce feed costs for cultivation and are able to accelerate the growth of biota to be cultivated and determine the results of profit comparisons between cultivation using nutritional formulas and not using nutritional formulas. This research applies descriptive approach method by means of observation and interviews and business feasibility analysis including income, TR (Total Revenue), BEP (Break Event Point), PBP (Payback Period) and FRR (Financial Rate of Return). The results of this research indicated that the provision of nutrients in biofloc system vaname shrimp farming can maximize the benefits of cultivation, BEP and PBP are also much faster and FRR > Bank interest rates.